Magnesium-doped coralline hydroxyapatite / tannic acid composite film and preparation method and application thereof

Magnesium-doped coral hydroxyapatite/tannin composite film was prepared through pulsed laser and low-energy electron beam deposition technology, which solved the problem of magnesium ion concentration control and long-term inhibition of bone tumors, and achieved biocompatibility and bone growth. Promote, significantly improve the effect of bone repair and tumor inhibition.

CN118480763BActive Publication Date: 2024-12-24NANJING UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410496798.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-03-25
Filing Date
2024-04-24
Publication Date
2024-12-24
Estimated Expiration
2044-04-24

AI Technical Summary

Technical Problem

In bone defect repair and bone tumor treatment, the prior art is difficult to effectively control the concentration of magnesium ions, resulting in biological defects, and at the same time it is difficult to achieve the effect of long-term inhibition of bone tumors.

Method used

The magnesium-doped coral hydroxyapatite film was prepared by pulsed laser deposition technology, and tannin was added through low-energy electron beam deposition technology to form a magnesium-doped coral hydroxyapatite/tannin composite film, with strong binding force and magnesium doping. Miscellaneous layers promote osteogenesis, and tannin layer slowly releases to inhibit bone tumors.

Benefits of technology

The biocompatibility and long-term effect of magnesium-doped coral hydroxyapatite/tannin composite films were achieved, while promoting bone growth and repair, avoiding changes in drug molecular composition and basal shape.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118480763B_ABST
    Figure CN118480763B_ABST
Patent Text Reader

Abstract

The present invention discloses a magnesium-doped coral hydroxyapatite / tannic acid composite film and a preparation method and application thereof. The method first uses pulsed laser deposition technology to deposit a magnesium-doped coral hydroxyapatite film on a substrate, and then uses low-energy electron beam deposition technology to deposit a tannic acid film on the magnesium-doped coral hydroxyapatite film to obtain a magnesium-doped coral hydroxyapatite / tannic acid composite film. The composite film prepared by the present invention has a strong membrane-substrate bonding force, a controllable film thickness, and the release of tannic acid in the upper layer can effectively inhibit bone tumors; the bottom magnesium-doped coral hydroxyapatite film, based on the rapid corrosion of magnesium in simulated body fluids, accelerates the formation of pores, induces biomineralization behavior, and promotes the formation of new bones, and has good application prospects in the treatment of bone tumors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomimetic materials and relates to a magnesium-doped coral hydroxyapatite / tannic acid composite film and a preparation method and application thereof. Background Art

[0002] Coral hydroxyapatite (CHA) has a similar composition and structure to natural bone and retains the porous structure of coral, which gives it good osteoconductivity and bioabsorption properties. Among them, the trace elements contained in coral hydroxyapatite, such as magnesium and strontium, promote bone growth. These trace elements have an important influence on the absorbability and calcification process of coral hydroxyapatite. Compared with ordinary hydroxyapatite, coral hydroxyapatite has an effectively uniform density and three-dimensional pore structure, while maintaining better support capacity and trabecular structure, which means that coral hydroxyapatite can not only be used as a bone defect repair material, but also play an additional drug release function during the treatment process. Literature 1 reported that coral hydroxyapatite transformed by hydrothermal treatment can be used for bone growth and repair, and gentamicin is added to the hydrothermal transformed coral powder for the delivery of antimicrobial drugs (The synthesis of hydroxyapatite from artificially grown Red Sea hydrozoan coral for antimicrobacterial drug delivery system applications. Ipek Karacan, Nathan Cox, Annette Dowd, et al, Journal of the Australian Ceramic Society, Pub Date: 2021-01-05). Overall, coral hydroxyapatite, as an artificial bone material, has potential in the field of bone defect repair and provides a viable option for bone reconstruction.

[0003] Magnesium is the fourth most abundant element naturally present in human bones and one of the essential ions in the body. Magnesium metal has good biocompatibility and osteogenic activity, and can promote the adhesion, growth and formation of bone matrix of osteoblasts during bone tissue development. Adding magnesium ions to intrabone implant materials can effectively promote the formation of new bones and have an important effect on the crystallization and biodegradation of mineral substances (Flame-sprayed strontium-and magnesium-dopedhydroxyapatite on titanium implants for osseointegration enhancement, Jheng-Yang Wang, Yu-Cheng Liu, Geng-Sheng Lin, et al, Surface & Coatings Technology, PubDate: 2020-02-08). However, it should be noted that when the concentration of magnesium ions is too high, it may cause biological defects of intrabone implant materials. Therefore, when using magnesium-containing calcium phosphate materials for bone tissue repair, it is necessary to control the concentration of magnesium ions to ensure the biocompatibility and safety of the material.

[0004] Tannic acid (TA) is a widely distributed natural polyphenolic compound. Tannic acid inhibits cell growth in various types of cancer, including breast cancer, prostate cancer, etc. The excellent structural and functional properties of polyphenolic hydroxyl groups based on tannic acid are of great value, especially in orthopedic transplantation. Importantly, tannic acid is cheap and easy to obtain. The team has already conducted some research on tannins in the early stage to inhibit bone tumors (Investigating the effect of tannin films prepared by low-energy electron beam deposition on the inhibition of bone tumors, Xiaoxue Tan, Hao Chen, Xin Liu, et al, Applied Surface Science, PubDate: 2024-03-01). Summary of the invention

[0005] The purpose of the present invention is to provide a magnesium-doped coralline hydroxyapatite / tannic acid composite film and a preparation method and application thereof. The method first uses pulsed laser deposition technology to prepare a magnesium-doped coralline hydroxyapatite film, and then uses the film as a substrate to prepare a tannin film using low-energy electron beam deposition technology, thereby obtaining a magnesium-doped coralline hydroxyapatite / tannic acid composite film.

[0006] The technical solution for achieving the purpose of the present invention is as follows:

[0007] The preparation method of magnesium-doped coralline hydroxyapatite / tannic acid composite film comprises the following specific steps:

[0008] Step 1: Grind coral hydroxyapatite powder and magnesium powder until fully mixed, and then press them into magnesium-doped coral hydroxyapatite targets. After fixing the targets and substrates, evacuate to 5-6×10 -4 Pa, pulsed laser deposition (PLD) was used to deposit magnesium-doped coralline hydroxyapatite films on the substrate. The pressure during the deposition process was controlled at 2 to 3 × 10 -3 Pa, and rotate the target at a speed of 25-30 r / min to prevent the target from being pierced by the laser, and the deposition time is 120±5 min;

[0009] Step 2: Using tannic acid powder as the target, vacuumize to 5-6×10 - 4 Pa, an electron beam is continuously irradiated on the target material in a vacuum chamber, the working current of the electron beam is 9.5±0.6A, and the working current is 0.9±1.2KV. A tannic acid film is deposited on the magnesium-doped coral hydroxyapatite film obtained in step 1 to obtain a magnesium-doped coral hydroxyapatite / tannic acid composite film.

[0010] Preferably, in step 1, the substrate is selected from a titanium sheet or a silicon sheet.

[0011] Preferably, in step 1, a Nd:YAG solid laser with a wavelength of 1064 nm, a pulse duration and a repetition frequency of 18 ns and 10 Hz respectively is used.

[0012] Preferably, in step 1, the mass ratio of magnesium powder to coral hydroxyapatite is 1:1.

[0013] Preferably, in step 2, the mass of tannic acid powder is 1.2 g.

[0014] The invention provides a magnesium-doped coralline hydroxyapatite / tannic acid composite film prepared by the preparation method.

[0015] Furthermore, the present invention provides the use of the above-mentioned magnesium-doped coralline hydroxyapatite / tannic acid composite film in the preparation of bone tumor treatment materials.

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] (1) Using pulsed laser deposition technology, the corresponding target material can be prepared by changing the stoichiometric ratio of magnesium and coralline hydroxyapatite, thereby obtaining ideal surface properties such as film thickness, morphology, and chemical composition.

[0018] (2) The low-energy electron beam deposition technology used is easy to operate and prepare, thereby forming a pollution-free film without affecting the shape and strength of the substrate itself; avoiding changes in the molecular composition of the drug.

[0019] (3) The magnesium-doped coral hydroxyapatite / tannic acid composite film prepared by the present invention has a strong binding force, and the tannic acid layer is slowly released, which can achieve the effect of long-term inhibition of bone tumors; at the same time, the magnesium-doped coral hydroxyapatite layer quickly forms pores in about 1 day, and a new apatite layer is formed on the surface in 14 days, which plays a role in promoting osteogenesis.

[0020] (4) The preparation method of the present invention is simple, rapid, low-cost, highly repeatable, and convenient for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 These are scanning electron microscope images of the samples, where a is Example 1, b is Comparative Example 1, c is Comparative Example 2, d is Comparative Example 3, and e is Comparative Example 4.

[0022] Figure 2 Graph showing the bonding force of the film, where a is Example 1, and b is Comparative Example 4.

[0023] Figure 3 Contact angle diagrams of the samples, where a is Example 1, b is Comparative Example 1, c is Comparative Example 2, d is Comparative Example 3, and e is Comparative Example 4.

[0024] Figure 4 The UV-visible absorption spectra of tannic acid released from Example 1 and Comparative Example 4 after immersion in SBF for different time periods are shown, wherein a is the standard concentration curve of tannic acid, and b is the dynamic release curve of tannic acid in the film.

[0025] Figure 5 Ca after being immersed in SBF for different time periods for Example 1 and Comparative Example 4 2+ and Mg 2+ Inductively coupled plasma-mass spectrometry of the release.

[0026] Figure 6 These are scanning electron microscope images of the film immersed in SBF for 1d, 3d, 7d, and 14d, where a is Example 1, and b is Comparative Example 4.

[0027] Figure 7 These are in vitro cell experiment diagrams of Example 1 and Comparative Example 1, including live / dead fluorescence staining of A-BMSCs cells after co-culture with the sample for 1d and 3d, ALP staining of B-BMSCs cells after osteogenic induction with the sample for 7d and 14d, and live / dead fluorescence staining of C-HOS cells after co-culture with the sample for 1d and 3d.

[0028] Figure 8These are in vitro cell experiment diagrams of Example 1 and Comparative Example 4, including the osteogenesis promotion and live / dead fluorescence staining experiment diagrams of A-BMSCs cells co-cultured with samples for 24h and 72h; and the tumor inhibition and live / dead fluorescence staining experiment diagrams of B-HOS cells co-cultured with samples for 24h and 72h. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with the embodiments and drawings.

[0030] Example 1

[0031] (1) Cleaning and drying of substrate

[0032] Before coating, the titanium and silicon wafers were cut into regular substrates of 2 cm × 3 cm, and washed with deionized water and anhydrous ethanol for 30 min, respectively, and repeated three times. After washing, they were placed in an oven at 70° for drying.

[0033] (2) Deposition of magnesium-doped coralline hydroxyapatite film

[0034] Weigh 1.5g coral hydroxyapatite and 1.5g magnesium powder (weight ratio = 1:1) and grind them until they are fully mixed, and then press them into magnesium-doped coral hydroxyapatite targets. Pulsed laser deposition technology was used, using a Nd:YAG solid laser with a wavelength of 1064nm, a pulse duration of 18ns and a repetition frequency of 10Hz. After the target and substrate were fixed, the vacuum pressure was maintained at 5-6×10 -4 Pa. During the deposition process, the pressure was controlled at 2 to 3 × 10 -3 Pa, and the target was rotated at a speed of 25-30 r / min to avoid the target being pierced by the laser. The deposition time was 120±5 min to obtain magnesium-doped coralline hydroxyapatite film.

[0035] (3) Deposition of magnesium-doped coralline hydroxyapatite / tannic acid composite film

[0036] Weigh 1.2 g of tannic acid powder and compact it in a crucible. Use low-energy electron beam deposition technology to evacuate the crucible to a vacuum of 5-6×10 -4 Pa, an electron beam is continuously irradiated on the target material in a vacuum chamber, the working current of the electron beam is 9.5±0.6A, and the working current is 0.9±1.2KV. A tannic acid film is deposited on the magnesium-doped coral hydroxyapatite film obtained in step 1 to obtain a magnesium-doped coral hydroxyapatite / tannic acid composite film.

[0037] The prepared magnesium-doped coralline hydroxyapatite / tannic acid composite film was characterized by SEM, binding force, contact angle, UV, ICP-MS, as well as osteoblast experiments and bone tumor cell inhibition experiments.

[0038] Comparative Example 1

[0039] This comparative example is a blank titanium sheet. The titanium sheet was cut into a regular substrate of 2 cm × 3 cm, and washed with deionized water and anhydrous ethanol for 30 minutes, respectively, and repeated three times. After drying, SEM, contact angle characterization, osteoblast experiment and bone tumor cell inhibition experiment were performed.

[0040] Comparative Example 2

[0041] This comparative example is a magnesium-doped coralline hydroxyapatite film. The specific steps are the same as those in (1) of Example 1. The magnesium-doped coralline hydroxyapatite film is subjected to SEM and contact angle characterization.

[0042] Comparison column 3

[0043] This comparative example is a tannic acid film. The specific steps are the same as those in (2) of Example 1. The tannic acid film is subjected to SEM and contact angle characterization.

[0044] Comparative Example 4

[0045] This comparative example is a magnesium-doped coral hydroxyapatite-doped tannic acid multi-doped monolayer film. The specific steps different from those in Example 1 are that the magnesium-doped coral hydroxyapatite target and 1.2g of tannic acid powder are placed in a vacuum chamber together, and pulsed laser deposition and low-energy electron beam deposition are turned on at the same time to bombard the magnesium-doped coral hydroxyapatite target and tannic acid powder, respectively, thereby obtaining a magnesium-doped coral hydroxyapatite-doped tannic acid monolayer film. The magnesium-doped coral hydroxyapatite-doped tannic acid monolayer film is characterized by SEM, binding force, contact angle, UV, and ICP-MS.

[0046] Figure 2 It is a bonding force diagram of Example 1 and Comparative Example 4. It can be seen from the figure that the film-substrate bonding force of Example 1 is 39.95N, and the bonding force of Comparative Example 4 is 44.23N; this is closely related to the composite form of the film.

[0047] Figure 3 is a contact angle graph. The contact angles of a, b, c, d and e in the figure are 18.24°±3.91°, 90.41°±2.55°, 91.65°±1.03°, 21.93°±0.89° and 93.79°±5.61° respectively. Example 1 Since the surface is tannic acid corresponding to Comparative Example 3, the hydrophilic surface can promote cell adhesion, while Comparative Example 4 is a monolayer film of magnesium-doped coral hydroxyapatite doped with tannic acid is hydrophobic.

[0048] from Figure 4 It can be seen that Example 1 shows a stable release of tannic acid as a whole, while in Comparative Example 4, tannic acid is released slowly within one day, starts to be released explosively after one day, and then tends to be stable. Figure 5It can be seen that the amount of calcium and magnesium ions released in Example 1 is higher than that in Comparative Example 4, which is more conducive to the formation of pores and further promotes osteogenesis. Compared with drugs and the long-term release of calcium and magnesium ions, Example 1 has more advantages. Figure 6 From the SEM images of Example 1 and Comparative Example 4, it can be found that the tannic acid on the surface of Example 1 is slowly released, exposing the underlying part of the magnesium-doped coralline hydroxyapatite film, so that calcium and magnesium ions are gradually released and exchanged with the ions in SBF. Sparse pores appear at 1d. With the release of tannic acid, the surface pores increase significantly at 7d. At 14d, the surface is covered with hydroxyapatite and a small amount of tannic acid continues to be released.

[0049] Figure 7 In group A, the cell survival rate of cells co-cultured with magnesium-doped coral hydroxyapatite / tannin composite film (Mg+CHA / TA) was significantly higher than that of blank Ti through live-dead fluorescence staining; ALP activity can reflect the differentiation level of osteoblasts, and group B showed that Mg+CHA / TA film had good ALP activity, further indicating that Mg+CHA / TA film can induce pre-osteoblasts to differentiate into osteoblasts; the live-dead fluorescence staining results of group C showed that with the extension of culture time, the number of attached cells and proliferating HOS cells on the Ti surface increased significantly. In contrast, only a small number of HOS cells adhered to the surface of the Mg+CHA / TA film sample. This observation further indicates that Mg+CHA / TA film has a significant inhibitory effect on HOS cells. In summary, magnesium-doped coral hydroxyapatite / tannin composite film can fully inhibit tumors and promote osteogenesis.

[0050] Figure 8 Figure A in the middle is the effect of Example 1 and Comparative Example 4 on BMSCs cell viability evaluated by CCK-8 detection method. The results show that both samples have no obvious cytotoxicity to normal osteoblasts, do not affect the proliferation of BMSCs cells, and the Mg+CHA / TA double-layer composite film has a better effect of promoting osteogenesis. Similarly, in the results of dead and live fluorescence staining, BMSCs cells proliferate well with the extension of culture time. The CCK-8 experimental results in Figure B show that both samples have the effect of inhibiting HOS cells, and the inhibitory effect of Mg+CHA / TA is more obvious. In the dead and live fluorescence staining, more dead cells (red) were found in Mg+CHA / TA, which is consistent with the CCK-8 results. In summary, the comparison between Example 1 and Comparative Example 4 found that Example 1 has a more obvious effect of promoting osteogenesis and inhibiting bone tumors.

Claims

1. A method for preparing a magnesium-doped coralline hydroxyapatite / tannic acid composite film, characterized in that: The specific steps are as follows: Step 1: Grind coral hydroxyapatite powder and magnesium powder until fully mixed, and then press them into magnesium-doped coral hydroxyapatite targets. After fixing the targets and substrates, evacuate to 5~6×10 -4 Pa, pulsed laser deposition technology was used to deposit magnesium-doped coralline hydroxyapatite films on the substrate. The pressure during the deposition process was controlled at 2~3×10 -3 Pa, and rotate the target at a speed of 25-30 r / min to prevent the target from being pierced by the laser, and the deposition time is 120 ± 5 min; Step 2: Using tannic acid powder as the target, vacuumize to 5~6×10 -4 Pa, an electron beam is continuously irradiated on the target material in a vacuum chamber, the working current of the electron beam is 9.5±0.6 A, and the working current is 0.9±1.2 KV. A tannic acid film is deposited on the magnesium-doped coral hydroxyapatite film obtained in step 1 to obtain a magnesium-doped coral hydroxyapatite / tannic acid composite film.

2. The preparation method according to claim 1, characterized in that: In step 1, the substrate is selected from a titanium sheet or a silicon sheet.

3. The preparation method according to claim 1, characterized in that In step 1, a Nd:YAG solid-state laser with a wavelength of 1064 nm, a pulse duration of 18 ns and a repetition frequency of 10 Hz was used.

4. The preparation method according to claim 1, characterized in that: In step 1, the mass ratio of magnesium powder to coral hydroxyapatite is 1:

1.

5. The preparation method according to claim 1, characterized in that: In step 2, the mass of tannic acid powder is 1.2 g.

6. The magnesium-doped coralline hydroxyapatite / tannic acid composite film prepared according to the preparation method described in any one of claims 1 to 5.

7. Use of the magnesium-doped coralline hydroxyapatite / tannic acid composite film according to claim 6 in preparing bone tumor treatment materials.

Citation Information

Patent Citations

  • Magnesium alloy implant composite material and preparation method and application thereof

    CN106902391A

  • Preparation method of polylactic acid-based ciprofloxacin / hydroxyapatite composite coating

    CN111359014A

  • Bone graft with a tannin-hydroxyapatite scaffold and stem cells for bone engineering

    US20180071433A1